I've answered this question but I can't get e right (I assume j'(m)*k'(m)=l'(m), but I can't make it work).

$\displaystyle GIVEN: j(m)=2m^2+m-6, k(m)=m^3+4$

a. Calculate j'(m) and k'(m)

$\displaystyle j'(m)=4m+1, k'(m)=3m^2$

b. l(m)=j(m)*k(m), work out a polynomial expression for l(m).

$\displaystyle l(m)=2m^5+m^4-6m^3+8m^2+4m-24$

c. Calculate l'(m)

$\displaystyle l'(m)=10m^4+4m^3-18m^2+16m+4$

d. Calculate j'(m)*k'(m)

$\displaystyle 12m^2+3m$

e. What do you notice about your answers to parts c and d?

...

I see no corrilation, that's why I need help. I think I didn't work out a polynomial properly? If someone could explain that'd be great.